Development Of Texture Enhancement Manufacturing Text Based On Language Coordination For State Elementary School Students - Renni Ramadhani Lubis (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2020)
This study aims to (1) analyze the need for developing enrichment books to produce negotiating text based on politeness according to students and teachers' perceptions, (2) describe the principles of enrichment book development, (3) produce prototype enrichment books, and (4) describe assessment and prototype repair. The research was conducted by the research and development method in five stages, namely a preliminary survey, initial prototype development, product design, product validation, and design improvement. The results of this study indicate that this enrichment book is appropriate to be used as a companion book in learning. This can be seen from the average value of the results of the test of verification by Indonesian language teachers in class of 82.50 which is included in the category of good and expert lecturers at 71.75 which is included in the quite good category